197 Acute Management of Traumatic Anterior Shoulder Dislocations During COVID-19: Are We Meeting Published National Standards for Treatment During the Pandemic?. (4th May 2021) - Donovan, R; Abdelmalek, A; Crowther, M; Packham, I
Abstract: Background: BESS/BOA Patient Care Pathways provide national guidelines for acute management of traumatic anterior shoulder dislocations with respect to emergency reduction and clinic follow-up. COVID-19 posed challenges in terms of analgesia choice for reductions and altered follow-up arrangements. This study aimed to assess variance from the care pathway. Method: We performed a retrospective case note analysis of all emergency presentations with acute traumatic anterior shoulder dislocations at the MTC in Bristol from 01/04/2019-31/05/2019 to the same period in 2020 to analyse the effects of COVID-19 on management of these injuries. Results: We identified 32 patients in 2019, and 24 in 2020. Entonox usage fell, in favour of Penthrox. Use of conscious sedation (requiring full PPE) remained around 20%. Pre- and post-reduction imaging was near 100% throughout. Referral to follow-up was 88% in 2019 but 38% in 2020. Those assessed in clinic during COVID-19, fewer were mobilised early or referred to outpatient physiotherapy compared to 2019. Conclusions: Acute management of anterior shoulder dislocations during COVID-19 was challenged by choice of suitable analgesia that limits AGPs, and limiting access to 'face-to-face' follow-up. A key concern was a significant decrease in patient follow-up, thus limiting the access to optimal aftercare such as physiotherapy and further imaging.